Elasticity of the Polish Labour Market - a Dynamic Analysis - Jadamus-Hacura, Maria; Melich-Iwanek, Krystyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper looks at the elasticity of the Polish labour market in the years 2002-2012. It first discusses the notion and role of labour market deregulation in the contemporary economy. It goes on to examine the scale and dynamics of the elasticity of the Polish labour market, described with 10 fragmentary indicators. Research was conducted with three synthetic measures and changes in their value in time were compared.